2015
DOI: 10.1080/10426914.2015.1058947
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of EDM Parameters on Machining Si3N4–TiN Composite for Improving Circularity, Cylindricity, and Perpendicularity

Abstract: The dominance of the spark eroding process in complex ceramic components has promoted a significant growth analysis in the ceramic composites domain in modern manufacturing industries. The latest developments in ceramic components are concentrated on both the enhancement of the mechanical properties and the machinability of complex 3D parts while using spark EDM. The current (I), pulse on time (T on ), pulse off time (T off ) and dielectric flushing pressure (DP) are considered sparking parameters for the mach… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(20 citation statements)
references
References 17 publications
(23 reference statements)
0
20
0
Order By: Relevance
“…Grey relational study is a way of converting two or more output parameters into a single output parameter so as to change the multi-response problem into a singleresponse one [25]. The method of grey relational study is explained in the subsections [26,27].…”
Section: Grey Relational Analysis Proceduresmentioning
confidence: 99%
“…Grey relational study is a way of converting two or more output parameters into a single output parameter so as to change the multi-response problem into a singleresponse one [25]. The method of grey relational study is explained in the subsections [26,27].…”
Section: Grey Relational Analysis Proceduresmentioning
confidence: 99%
“…The bottom interelectrode gap was also manipulated by applying ultrasonic vibrations in the vertical direction [3], [5] and [6]. Moreover, it is reported that increasing electrode rotation [7] to [9] and dielectric pressure [10] to [12] have provided improvements in flushing and drilling performance. In contrast, only a few studies have been conducted for investigating the effect of electrode shape in the EDD process.…”
Section: Introductionmentioning
confidence: 99%
“…Electrical discharge machining (EDM) is a cheap and flexible way of mechanical processing, by which materials to be machined need to be conductive (electric conductivity > 2.0 × 10 2 S·cm −1 , with resistivity of <5 × 10 −3 Ω·cm) . Hence, tremendous efforts have been devoted to the research and development of Si 3 N 4 ‐based conductive ceramic by adding a second phase to meet the requirement of EDM, since Si 3 N 4 is an insulator (with resistivity of >10 11 Ω·cm) …”
Section: Introductionmentioning
confidence: 99%
“…4 Hence, tremendous efforts have been devoted to the research and development of Si 3 N 4 -based conductive ceramic by adding a second phase to meet the requirement of EDM, since Si 3 N 4 is an insulator (with resistivity of >10 11 ΩÁcm). [5][6][7][8] Among these family, titanium nitride (TiN) is considered to be a promising second phase due to its high electrical conductivity (with resistivity lower than 10 À3 ΩÁcm) and good physical properties, such as high hardness, chemical inertness, and low friction coefficient. [9][10][11] Unfortunately, TiN has poor oxidation resistance at high temperature, and oxidation occurs from 650°C resulting in the poor stability of the whole materials at high-temperature conditions.…”
Section: Introductionmentioning
confidence: 99%